Changes of protein stiffness during folding detect protein folding intermediates. - Małek, Katarzyna E.; Szoszkiewicz, Robert (My University, 2014)
Single-molecule force-quench atomic force microscopy (FQ-AFM) is used to detect folding intermediates of a simple protein by detecting changes of molecular stiffness of the protein during its folding process. Those stiffness changes are obtained from shape and peaks of an autocorrelation of fluctuations in end-to-end length of the folding molecule. The results are supported by predictions of the equipartition theorem and agree with existing Langevin dynamics simulations of a simplified model of a protein folding. In the light of the Langevin simulations the experimental data probe an ensemble of random-coiled collapsed states of the protein, which are present both in the force-quench and thermal-quench folding pathways.
Keywords: STM and AFM manipulations of a single molecule; Folding: thermodynamics, statistical mechanics, models, and pathways; Mechanical properties of molecules